Pengembangan Model Pembelajaran Kolaboratif untuk Peningkatan Hasil Belajar Gambar Teknik di Sekolah Menengah Kejuruan - Zainur Rofiq Rofiq; Urip Widodo; Dandhi Fajartanni (Faculty of Engineering, Universitas Negeri Yogyakarta, 2014)
The objective of the study is to find out the effect of the instructional model and the cognitive style on the Vocational High School students’ learning outcomes. The model of this study was collaborative and direct. The students’ cognitive style were field independent and field dependent types. This study was conducted in SMKN 3 Yogyakarta by using the 2x2 factorial experiment design. The samples were 132 students of SMKN 3 Yogyakarta who were selected by multistage random sampling. The results of the study showed that (1) the learning outcomes of the students treated with the collaborative model is higher than those who were treated with the direct model in the subject of interpreting technical drawing (2) there was a significant interactional effect between the instructional model and the cognitive style, (3) the learning outcomes of field independent students who were treated with the collaborative model were higher than those who were treated with the direct model, (4) the learning outcomes of field dependent students who were treated with the collaborative model were not significantly different than those who were treated with the direct model.